Qur'anic Mindfulness Innovation PAI approach in Responding Generation Z 's Mental Health Crisis - Nurkamariah Nurkamariah (Fitrah, 2025)
Crisis Mental health of Generation Z in the era of digital disruption characterized by the phenomena of social comparison and fragmentation soul demand repositioning of Islamic Religious Education (PAI) from just aspect cognitive become instrument psycho -spiritual research This aim For formulating an PAI integration model based on Qur'anic Mindfulness as an intervention strategy mental crisis through method qualitative type studies library research with technique analysis content analysis of literature Islamic psychology and spirituality for the period 2020-2025. Analysis results show that Qur'anic Mindfulness works through the "Golden Triangle of Spiritual Well-being" mechanism which includes Dhikr as anchor ontological stabilizer system limbic, Fikr through contemplation as framework cognitive decognition negative, and Charity as actualization behavior adaptive, which is neuropsychological capable regulate amygdala For reach nafs al- mutmainnah . Contribution scientific study This lies in the originality of the intervention model that diverts focus individual from validity external digital towards transcendental internal validity . The implication is that the Islamic Religious Education curriculum needs to transform become means spiritual therapy through technique literacy practical psycho -spiritual like "Pause and Pray" method for build spiritual immunity of students in the midst of disruptive dynamics of the times.